2016
DOI: 10.3389/fphar.2016.00270
|View full text |Cite
|
Sign up to set email alerts
|

Shikonin Inhibits Intestinal Calcium-Activated Chloride Channels and Prevents Rotaviral Diarrhea

Abstract: Secretory diarrhea remains a global health burden and causes major mortality in children. There have been some focuses on antidiarrheal therapies that may reduce fluid losses and intestinal motility in diarrheal diseases. In the present study, we identified shikonin as an inhibitor of TMEM16A chloride channel activity using cellbased fluorescent-quenching assay. The IC 50 value of shikonin was 6.5 µM. Shortcircuit current measurements demonstrated that shikonin inhibited E act -induced Cl − current in a dose-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 36 publications
1
28
0
2
Order By: Relevance
“…Although the role of CLCs in renal physiology is not clear (97), excessive amounts of chlorine aggravate cell damage. The shikonin in the herbal medicine is said to be a CLC inhibitor (98). In the current study, one of the flavonoids, troxerutin, had rescue effects on OTA-induced CLC activation.…”
Section: Discussionsupporting
confidence: 48%
“…Although the role of CLCs in renal physiology is not clear (97), excessive amounts of chlorine aggravate cell damage. The shikonin in the herbal medicine is said to be a CLC inhibitor (98). In the current study, one of the flavonoids, troxerutin, had rescue effects on OTA-induced CLC activation.…”
Section: Discussionsupporting
confidence: 48%
“…Inhibition of saliva production and dry mouth may occur mediation with TMEM16A-inhibitors (Ousingsawat et al, 2009; Catalan et al, 2015). Inhibition of TMEM16A may also attenuate intestinal contraction and abdominal peristalsis (Sanders et al, 2012; Singh et al, 2014), and therefore could have antidiarrheal effects (Tradtrantip et al, 2010; Namkung et al, 2011b; Jiang et al, 2016). Finally, inhibition of renal TMEM16A could potentially lead to proteinuria and acidosis (Faria et al, 2014; Schenk et al, 2018).…”
Section: Biological Effects Of Inhibitors and Activators Of Tmem16amentioning
confidence: 99%
“…This multi-faceted control of Ca 2+ signalling suggests a crucial role for Ca 2+ channels in the pathophysiology of RV. In this regard, it was shown that the blockade of CaCCs, including TMEM16A, reduces intestinal motility and fluid loss in vivo with no direct effects on the levels of virus infection [74].…”
Section: Viral Channelopathies and Ca 2+ Channelsmentioning
confidence: 99%